Emerging site-specific bioconjugation strategies for radioimmunotracer development. (2nd August 2016) - Massa, Sam; Xavier, Catarina; Muyldermans, Serge; Devoogdt, Nick
ABSTRACT: Introduction : Radioimmunotracers are a promising class of companion diagnostics for precision medicine. They are composed of an antibody-based targeting agent and a radiolabeled imaging probe. Together with the tendency towards the use of small antibody-derived fragments, the employed conjugation method is gaining increasing attention. Conventional bioconjugation methods result in heterogeneous tracer populations of which the single elements can differ in immunoreactivity, pharmacokinetic behavior and stability. Site-specific conjugation strategies try to overcome these shortcomings and facilitate radioimmunotracer delivery, characterization and manufacturing. Areas covered : An overview is provided of site-specific conjugation strategies for use in radioimmunotracer development. Currently applied strategies are discussed, together with other emerging site-specific conjugation methods that are applicable to diabodies, single-chain variable fragments (scFvs) and camelid single-domain antibody-fragments (sdAbs or nanobodies). Expert opinion : The ultimate goal of site-specific bioconjugation strategies is to allow precise control over the conjugation site, to result in homogenous tracer populations, and to be versatile in use with different imaging probes. Chemoenzymatic methods appear to be promising in this respect.